Annual Plan 2002-03 Background Note 2002-03 - Planning Commission (Planning Commission, 2002)
Spread over an area of 2.75 lakh sq.km, the State of Andhra Pradesh as per census 2001 the State has a population of 7.57 crore. It ranks fifth largest State in terms of area, as well as, population. the decadal growth rate of population 13.86% during 1991-2001 is considerably lower than the corresponding all India decadal growth rate of 21.34%. The sex ratio in the State has improved and was for the first time stands at 978 as against all India average of 933. the density of population at 275 is much lower than the all India average of 324.
Planning Commission, State Plan Division